PEDAGOGICAL MATERIAL PROPOSAL FOR ASSESSING ELEMENTARY MATHEMATICS STUDENTS WITH CEREBRAL PALSY - Silva, M. Oliveira da; Manzini, E. Jose [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education A& Development, 2013)
Planning an activity and adapting a pedagogic resource for students with cerebral palsy requires assessing their physical, cognitive and sensory characteristics. However, the Special Education professional may find difficulties in assessing those characteristics especially because the students' potential may be camouflaged by their motor limitations. In this context, Silva developed an assessment tool entitled Protocol for prescribing or adapting pedagogic resources for students with cerebral palsy in 2010. This material was prepared with the objective of assisting the special education professional in assessing students with cerebral palsy enrolled in elementary schools. Although the tool contributes to identify the strengths and needs of the students, the professional has to choose their own pedagogic materials to assess the student, which could prevent its use. In order to make viable the use of the tool, the objective of this study was to propose pedagogic materials to be used for the assessment of elementary mathematics students with cerebral palsy and make adjustments to the instrument. For this, a set of pedagogic materials from the theoretical framework for assessing mathematical skills described in the instrument was collected and appointed. The proposed materials and the instrument were used to assess thirteen students with cerebral palsy. Every assessment session was filmed. From the analysis of the footage, it was possible to identify the teaching materials that contributed to assess the student and the skills that each material assessed (a total of thirteen teaching materials was used to assess fifty-three math skills). As for adjustments, by using the instrument it was possible to redefine some areas (new abilities were added, while others were modified or excluded). In the studied cases, the use of the instrument and the materials above was useful so that the professional could perform an accurate assessment regarding the mathematical skills and difficulties of the students. The assessments contributed to the planning of subsequent activities and adaptation of teaching materials that were not accessible to the students, according to the motor characteristics of each one of them.
Keywords: Special Education; Assessment Protocol; Cerebral Palsy